Assessing the need for psychooncological support: screening instruments in combination with patients' subjective evaluation may define psychooncological pathways. Issue 12 (4th June 2015) - Schaeffeler, N.; Pfeiffer, K.; Ringwald, J.; Brucker, S.; Wallwiener, M.; Zipfel, S.; Teufel, M.
Abstract: Background: Cancer patients suffer from severe distress. About one third show mental comorbidities. Nevertheless, there is no common agreement on how to measure distress or identify patients in need for psychooncological services using screening questionnaires. Patients and methods: A sample of N = 206 patients with confirmed breast cancer, being inpatient for surgical treatment, filled in distress assessment instruments: Distress Thermometer, Hospital Anxiety and Depression Scale, Patient Health Questionnaire 2, Hornheider Screening Instrument and parts of the EORTC‐QLQ‐C30. Additionally, they were asked for their subjective need for psychooncological counselling. Results: The correlation between the assessment instruments is low to medium. The number of patients above the cut‐off criteria varies quite a lot according to the instrument (10% to 66%). Therefore, the congruence between the instruments' indications is quite low. Patients with and without subjective need do not differ in personal data but in distress scores. Conclusions: Recommended instruments for distress assessment in psychooncology measure different areas of distress. They do not sufficiently agree in indicating a patient's need for psychooncological treatment. Hence, one should neither compare results of studies using different assessment instruments nor implement a screening without reflecting the used instrument's characteristics compared to the others. The subjective need seems to provide additional information to the assessment. At present, the combination of an assessment instrument and patients' subjective need is seen as a best practice for identifying patients in need of psychooncological treatment. Copyright © 2015 John Wiley & Sons, Ltd.